Large Scale Fabrication of Ordered Gold Nanoparticle-Epoxy Surface Nanocomposites and Their Application as Label-Free Plasmonic DNA Biosensors - Lednický, Tomáš; Bonyár, Attila (ACS applied materials & interfaces, 2020)
A robust and scalable technology to fabricate ordered gold nanoparticle arrangements on epoxy substrates is presented. The nanoparticles are synthesized by solid-state dewetting on nanobowled aluminum templates, which are prepared by the selective chemical etching of porous anodic alumina (PAA) grown on an aluminum sheet with controlled anodic oxidation. This flexible fabrication technology provides proper control over the nanoparticle size, shape, and interparticle distance over a large surface area (several cm2), which enables the fine-tuning and optimization of their plasmonic absorption spectra for LSPR and SERS applications between 535 and 625 nm. The nanoparticles are transferred to the surface of epoxy substrates, which are subsequently selectively etched. The resulting nanomushrooms arrangements consist of ordered epoxy nanopillars with flat, disk-shaped nanoparticles on top, and their bulk refractive index sensitivity is between 83 and 108 nm RIU-1. Label-free DNA detection is successfully demonstrated with the sensors by using a 20 base pair long specific DNA sequence from the parasite Giardia lamblia. A red-shift of 6.6 nm in the LSPR absorbance spectrum was detected after the 2 h hybridization with 1 μM target DNA, and the achievable LOD was around 5 nM. The reported plasmonic sensor is one of the first surface AuNP/polymer nanocomposites ever reported for the successful label-free detection of DNA.
Keywords: Nanocomposites; zlato; Surface Plasmon Resonance; nanobowled aluminum; kovové nanočástice; localized surface plasmon resonance; DNA biosensor; Giardia lamblia; Gold; nanokompozity; DNA, Protozoan; povrchová plasmonová rezonance; Metal Nanoparticles; protozoální DNA; nanoparticle lattice; surface nanocomposite